G155(P) More than a break: the impact of changing local skeletal survey policy. (12th March 2018) - Jacob, H; Hewitson, R; Hann, G
Abstract : Aims: Given variations in practice, Wood et al. (2014) proposed criteria for undertaking a skeletal survey in children under two presenting with a fracture. We incorporated these criteria into our local hospital policy for performing skeletal survey. This study aimed to establish the impact of the new guidelines on the number of skeletal surveys performed and the yield of occult fractures. Methods: We conducted a retrospective casenote review over two consecutive years: the year before the change in the skeletal survey guideline and the year following its implementation. We reviewed the electronic records of all children under two presenting to the Emergency Department with a fracture and cross-checked this with all skeletal surveys performed in this age group. Those with finger or toe fractures were excluded. We recorded the child's age, the mechanism proposed and any delay in presentation. We noted the fracture type and whether a skeletal survey was, or should have been, performed. Any additional fractures were recorded. All records were reviewed by two researchers. Results: There were 108 records included: 64 before the policy change and 44 after. The children's mean age was 16 months (range 3 weeks to 23 months). Before the policy change, 5/64 (8%) children underwent skeletal survey and 13/44 (30%) afterwards. There was 1/64 (2%) additional fractures identified prior to the change and 3/44 (7%) afterwards. There were four children before the policy change who did not have a skeletal survey performed but would have qualified under the new guidelines. Conclusions: Implementing Wood's criteria increased the number of skeletal surveys performed threefold. Given the high yield of additional fractures found, we would encourage others to consider adopting this policy for skeletal survey in children under two to reduce the chance of missing occult fractures. Our experience demonstrates that such a policy is workable in a busy district general hospital.